Alterations in mitochondrial respiration and reactive oxygen species in patients poisoned with carbon monoxide treated with hyperbaric oxygen - Jang, David H.; Khatri, Utsha G.; Shortal, Brenna P.; Kelly, Matthew; Hardy, Kevin; Lambert, David S.; Eckmann, David M. (Intensive care medicine experimental, 2018)
Background Carbon monoxide (CO) poisoning is the leading cause of poisoning mortality and morbidity in the USA. Carboxyhemoglobin (COHb) levels are not predictive of severity or prognosis. At this time, the measurement of mitochondrial respiration may serve as a biomarker in CO poisoning. The primary objective of this study was to assess changes in mitochondrial function consisting of respiration and generation of reactive oxygen species (ROS) in peripheral blood mononuclear cells (PBMCs) obtained from patients with CO poisoning. Methods PBMCs from patients having confirmed CO exposure treated with hyperbaric oxygen or HBO (CO group) and healthy controls (control group) were analyzed with high-resolution respirometry. PBMCs were placed in a 2-ml chamber at a final concentration of 3–4 × 10 6 cells/ml to simultaneously obtain both respiration and hydrogen peroxide (H 2 O 2 ) production. In the CO group, we performed measurements before and after patients underwent their first HBO treatment. Results We enrolled a total of 17 subjects, including 7 subjects with confirmed CO poisoning and 10 subjects in the control group. The CO group included five (71.4%) men and two (28.6%) women having a median COHb of 28%. There was a significant decrease in respiration as measured in pmol O 2 × s − 1 × 10 − 6 PBMCs in the CO group (pre-HBO) when compared to the control group: maximal respiration (18.4 ± 2.4 versus 35.4 ± 2.8, P < 0.001); uncoupled Complex I respiration (19.8 ± 1.8 versus 41.1 ± 3.8, P < 0.001); uncoupled Complex I + II respiration (32.3 ± 3.2 versus 58.3 ± 3.1, P < 0.001); Complex IV respiration (43.5 ± 2.9 versus 63.6 ± 6.31, P < 0.05). There were also similar differences measured in the CO group before and after HBO treatment with an overall increase in respiration present after treatment. We also determined the rate of H 2 O 2 production simultaneously with the measurement of respiration. There was an overall significant increase in the H 2 O 2 production in the CO group after HBO treatment when compared to prior HBO treatment and the control group. Conclusions In this study, PBMCs obtained from subjects with CO poisoning have an overall decrease in respiration (similar H 2 O 2 production) when compared to controls. The inhibition of Complex IV respiration is from CO binding leading to a downstream decrease in respiration at other complexes. PBMCs obtained from CO-poisoned individuals immediately following initial HBO therapy displayed an overall increase in both respiration and H 2 O 2 production. The study findings demonstrate that treatment with HBO resulted in improved cellular respiration but a higher H 2 O 2 production. It is unclear if the increased production of H 2 O 2 in HBO treatment is detrimental.